Successful visual outcome following vitrectomy for complication of ocular tuberculosis - Norshamsiah, MD; Muhaya, M; Bastion, MLC (Department of Surgery, UKM Medical Centre, 2012)
A 24-year-old Chinese gentleman presented with two weeks history of sudden floaters in his right temporal visual field associated with blurring of vision. This ex-smoker also reported chronic, bloody cough for two years and recent pleuritic chest pain. Examination revealed a thin patient with right eye visual acuity of 6/18 associated with optic nerve dysfunction, optic disc swelling and macula star, retinal vasculitis and retinitis. Despite anti-tuberculosis medication and corticosteroids, he developed neovascularisation. Subsequent vitreous haemorrhage necessitated trans pars plana vitrectomy, membrane peeling, endolaser and silicone oil injection. Final visual acuity was 6/9 with quiescent retinopathy.